Endogamous Marriage in Sidoresmo, Surabaya City: A Structural-Functionalism Perspective - Khoiri, Muhammad Hilalul Khoiri; Ulya, Zakiyatul Ulya (Indonesian Association of Islamic Family Law Lecturers, 2024)
Problem statement: Endogamous marriage represents a multifaceted and heterogeneous phenomenon shaped by a variety of cultural and social determinants. Objective: This study seeks to examine the practice of endogamous marriage in Sidoresmo Dalam, Surabaya, through the framework of structural functionalism theory. The primary focus of this research is on the different forms and factors that influence the prevalence of endogamous marriage in this locality, as well as an analytical interpretation through the structural functionalist lens. Methods: This investigation employs field research utilizing a phenomenological approach, with data collection methods that include both observation and interviews. The analysis is conducted using qualitative methodologies. To ensure the validity of the data, triangulation techniques are implemented by comparing information obtained from multiple sources. Results: The findings reveal that there are two distinct forms of endogamous marriage in Sidoresmo Dalam, Surabaya: arranged marriages and non-arranged marriages. These forms of endogamous unions are influenced by five key factors: the preservation of lineage, the transmission of traditions across generations, parental authority, the practice of arranged marriages, and the principle of equality. When viewed through the lens of structural functionalism and employing the AGIL framework, the phenomenon of endogamous marriage in Sidoresmo Dalam, Surabaya illustrates the following: first, adaptation, where arranged marriages serve as a mechanism for conforming to communal cultural norms and principles; second, goal, wherein endogamous marriage seeks to foster harmony by minimizing identity conflicts and preserving lineage and family genealogy; third, integration, highlighting the pivotal role of parents in instilling familial values and driving the practice of endogamous marriage among close relatives; and fourth, pattern maintenance, suggesting that endogamous marriage will persist as a means of safeguarding and perpetuating lineage. Conclusion: Endogamous marriage in Sidoresmo Dalam, Surabaya, is a form of social adaptation maintained through the dominant role of parents and family traditions to preserve lineage, social equality, and social order within the framework of structural functionalism.